Ecological and economic bases for development and implementation of carbon sequestration related climate projects in Russia - Yulia L. Zakirova; Anastasia V. Lazareva (RUDN Journal of Ecology and Life Safety)
The article examines the emerging national carbon market in Russia, the incentives and competitive advantages of domestic business at the carbon market as the economic basis for development and implementation of carbon sequestration projects in Russia. The Russian Federation, which has committed itself to taking measures to mitigate climate change, has set a goal of achieving carbon neutrality by 2060 in two possible ways: through direct emissions reduction and carbon capture (sequestration), storage (deposition). The national carbon trading system being actively created in Russia allows the state to fulfill its international climate obligations, but at the same time act as an independent regulator in this area and proactively protect domestic producers from possible unfair competition and arbitrariness on the part of participants in the global carbon market.